Improving Road Safety at Blackspot Locations on Garuda Sakti Road in Pekanbaru - Br Pangaribuan, Lia Agistin; Ryanto, Stefanus Sylvan; Prasetyo, Hendrik (PT. Alpha Trianguli Australis, 2025)
Garuda Sakti Road is one of the roads in Pekanbaru City with the function of primary arterial road, city road status and becomes an access road to the CBD because it is directly adjacent to the CBD and becomes a connecting road between Pekanbaru City and Kampar Regency, so it has a high volume of vehicles and the spospeedt results show that it has a high vehicle speed as well. This road is an accident-prone area in a row for 3 years with 10 accidents in the last 5 years of accidents with land use is shops and there is a school safety zone. In the analysis of the existing conditions of the Garuda Sakti road section, it was found that the pavement was in a potholed, cracked condition and the road markings were faded and even had no markings. The purpose of this research is to provide recommendations based on the analysis of safe road aspects. These recommendations include improvements and installation of road safety facilities in order to create increased safety on road sections and can reduce the incidence of accidents and accident fatalities.